Pesantren Ramadan sebagai Bentuk Pembinaan kepada Masyarakat Desa Sicini Kabupaten Gowa Sulawesi Selatan - Chamdar Nur; Sulkifli Herman; Syandri Syandri (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2022)
The purpose of the STIBA Makassar Real Work Lecture (KKN) is part of a form of community service which is one of the three important pillars of a university, specifically the da'wah approach to the community by using a unique approach based on benefits, namely the activities of the Ramadhan Islamic Boarding School. The method of implementing the service program begins by conducting a study of the needs of the community from children to the elderly using SOAR analysis. After the analysis is carried out, the next step is the preparation of work programs needed by the community. Work programs that have been successfully implemented include: Islamic Boarding School Ramadhan, teaching TK/TPA, and Training for Organizing the Body. All programs are running well and have shown results in accordance with the planned KKN objectives, namely to make the people of Sicini Village a more religious community through special coaching during the month of Ramadan.